Neural Coding of Syllable-Final Fricatives with and without Hearing Aid Amplification - Miller, Sharon E.; Zhang, Yang (Journal of the American Academy of Audiology, 2020)
Abstract Background Cortical auditory event-related potentials are a potentially useful clinical tool to objectively assess speech outcomes with rehabilitative devices. Whether hearing aids reliably encode the spectrotemporal characteristics of fricative stimuli in different phonological contexts and whether these differences result in distinct neural responses with and without hearing aid amplification remain unclear. Purpose To determine whether the neural coding of the voiceless fricatives /s/ and /ʃ/ in the syllable-final context reliably differed without hearing aid amplification and whether hearing aid amplification altered neural coding of the fricative contrast. Research Design A repeated-measures, within subject design was used to compare the neural coding of a fricative contrast with and without hearing aid amplification. Study Sample Ten adult listeners with normal hearing participated in the study. Data Collection and Analysis Cortical auditory event-related potentials were elicited to an /ɑs/–/ɑʃ/ vowel-fricative contrast in unaided and aided listening conditions. Neural responses to the speech contrast were recorded at 64-electrode sites. Peak latencies and amplitudes of the cortical response waveforms to the fricatives were analyzed using repeated-measures analysis of variance. Results The P2' component of the acoustic change complex significantly differed from the syllable-final fricative contrast with and without hearing aid amplification. Hearing aid amplification differentially altered the neural coding of the contrast across frontal, temporal, and parietal electrode regions. Conclusions Hearing aid amplification altered the neural coding of syllable-final fricatives. However, the contrast remained acoustically distinct in the aided and unaided conditions, and cortical responses to the fricative significantly differed with and without the hearing aid.